Processing of Porous Glass Ceramic using Silica Sand and Industrial Waste for Tiling Application - Mohd Hakim Ibrahim; Mohd Idham Mustaffar; Anis Nadhirah Ismail; Syarifah Aminah Ismail; Nabihah Othman (International Journal of Nanoelectronics and Materials (IJNeaM), 2024)
The main goal of this research is to produce a porous glass ceramic from natural silica sources and industry waste to be used as tiling in building applications. Basically, silica sand is the raw material of natural silica while soda lime glass is the raw material of industrial silica. Both materials were mixed with carbonate foaming agent and clay binder. Then, the mixed samples were pressed into button shape. The button-shape samples were sintered at sintering temperatures of 800, 850, 900 and 950°C with natural cooling at room temperature for 24 hours. It was found that the highest bulk density and modulus of rupture (MOR) were obtained at 800°C with 1.91 g/cm3 and 21.97 MPa respectively, while the highest water absorption was obtained at 950°C with 16.37%. The surface morphology analysis showed that, as the temperature increased, the pores became larger and some of them merged and bonded together. However, the optimum sintering temperature was achieved at temperature 900°C recording to its lower density (1.75 g/cm3) and high MOR (19.64 MPa) that met the ISO 13006 standard's minimum requirement of higher than 15 MPa.